KEWENANGAN OTORITAS JASA KEUANGAN DI BIDANG PERBANKAN DALAM MEWUJUDKAN KEPASTIAN HUKUM - Supriatna, Ucu (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2018)
National banking is one of the main pillars in national economic development, and is expected to be an agent of development in achieving national goals, so that required a strong and professional institutions in the regulation and supervision of the banking and independent of the intervention of other parties. discusses the authority of the Financial Services Authority in conducting banking regulatory and supervision in Indonesia with the principles of legal certainty, the relationship between the Financial Services Authority and Bank Indonesia in regulating and supervising the banking and OJK Independence in regulating and supervising banking in Indonesia. The research method used in this research is analytical descriptive research method, that is research which describe and describe various state or fact whic h exist about Authority of Financial Services Authority In Banking in Realizing Legal Certainty. Then the general description is analyzed by starting from the legislation, the existing theories and the opinions of experts who aims to find and get answers from the main issues that will be discussed further and using the method of normative juridical approach, namely research methods that emphasize the secondary data that is by studying and reviewing the principles of law and positive law rules derived from the existing literature materials in legislation and other legal provisions. The results of the research on the authority of the Financial Services Authority in the Banking Division in realizing legal certainty, Before the establishment of OJKyang perform the tasks and functions of regulation and supervision of banks is Bank Indonesia, but after the establishment of OJK, the tasks and functions of banking regulation and supervision turned to OJK. Between Bank Indonesia and OJK can not be separated there is still a connection. Bank Indonesia conducts Macroprudential Supervision, which regulates the stability of the financial system as a whole and comprehensively, while OJK conducts microprodential surveillance, namely Regulation and supervision on institutional, health, prudential aspects, and bank checks. But in its implementation does not close the possibility of overlapping. With the contribution or levy of companies conducting business activities in the financial services sector will affect the level of independence of OJK itself, so that the dues or charges should not be charged to the company, but charged to the state budget so that there is no conflict interest. Keywords: Bank Regulation & Supervision, Legal Certainty, OJK Independence